A cobalt oxide nanocubes interleaved reduced graphene oxide nanocomposite modified glassy carbon electrode for amperometric detection of serotonin - Shahid, Muhammad Mehmood; Rameshkumar, Perumal; Numan, Arshid; Shahabuddin, Syed; Alizadeh, Mahdi; Khiew, Poi Sim; Chiu, Wee Siong (Elsevier, 2019)
Cobalt oxide nanocubes incorporated with reduced graphene oxide (rGO-Co 3 O 4 ) was prepared by using simple one-step hydrothermal route. Crystallinity and structural characteristics of the nanocomposite were analyzed and confirmed using X-ray diffraction (XRD) and Raman analysis, respectively. The cubical shape of the Co 3 O 4 nanostructures and the distribution of Co 3 O 4 nanocubes on the surface of rGO sheets were identified through field emission scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX) mapping analysis, respectively. Raman spectra depicted the presence of D and G bands for GO and rGO with different I D /I G values and thus confirmed the reduction of GO into rGO. The electrochemical study reflects that the rGO-Co 3 O 4 nanocomposite shows good electrocatalytic activity in oxidation of depression biomarker serotonin (5-HT) in phosphate buffer (pH 7.2). The detection of 5-HT was carried out by using rGO-Co 3 O 4 nanocomposite modified glassy carbon electrode under dynamic condition using amperometry technique with a linear range of 1–10 μM. The limit of detection and limit of quantification were calculated and found to be 1.128 and 3.760 μM, respectively with a sensitivity value of 0.133 μΑ·μM −1 . The sensor showed selectivity in the presence of different interferent species such as ascorbic acid, dopamine and uric acid. © 2019 Elsevier B.V.